A new species of Torrenticola ungeri complex (Acari, Hydrachnidia, Torrenticolidae), and new water mite records for Portugal - Pešić, Vladimir; Girão, Dinis; Vergata, Chiara; Silva, Luís P. Da; Ferreira, Sónia (Zootaxa, 2025)
A new species belonging to the Torrenticola ungeri complex, T. galaica sp. nov., is described from northwestern Portugal. It differs from other closely related congeners by its roundish idiosoma, distinctive dorsal shield shape and color pattern, and divergent DNA barcode sequences. Additionally, Torrenticola ungeri disparilis Walter, 1947, previously synonymized with T. ungeri ungeri (Szalay, 1927), is resurrected as a valid subspecies. New faunistic data from Portugal based on DNA barcoding are presented, with six species recorded for the first time for Portugal.